Model Deret Waktu Produksi Genteng Pejaten dalam Keterbatasan Sumber Daya - I Gusti Ayu Made Srinadi; Desak Putu Eka Nilakusmawati (Jurnal Matematika, 2018)
The sample of this research was taken by purposive sampling technique, the villagers of Pejaten who are tile craftsmen. Data was collected through a questionnaire filled with 105 tile craftsmen. The tile materials of Pejaten Village include clay and rocky soil, clay is currently almost 95% from outside the village of Pejaten. The clay supplier villages include Bantas Village, Selemadeg, Meliling, Jadi, Gadungan, and Pandak. Most of the coconut fiber fuel is mostly imported from Jembrana Regency. Some laborers in tile production are family members of craftsmen and most use wage labor. This condition shows the scarcity of tile production resources in Pejaten Village. This study aims to find out how tile production in Pejaten village is in a condition of limited resources, and how the forecasting model of tile production is based on historical data from January 2013 to December 2017. The results of in-depth interviews with several tile craftsmen state that they will continue to produce tile along the roof tile demand still exists and is able to provide raw materials even though most are imported from outside the Pejaten Village. The amount of tile production shows a seasonal trend, and the time series model that is most suitable for the number of tile production is the SARIMA (1,1,5) (1,1,1) 12 model.